Implementasi Dan Pemanfaatan Blended Learning Bagi Mahasiswa STMIK Pranata Indonesia - Salman Farizy; G. Andrianto (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract Entering the beginning of 2020 the world community was shocked by the corona virus outbreak (Covid19), the rapid spread and infected patients who were suspected of being able to spread through physical contact also through the air and could cause death caused the World Health Organization (WHO) to declare the world into a global emergency related this virus corona virus outbreak has had an impact on the education sector. Almost all students or students around the world are disrupted in their school activities or lectures and result in the threat of their educational rights in the future. By utilizing online technology it is hoped that all work can continue to be carried out to support work or the learning and teaching process. Implementation and Utilization of E-Learning where students and lecturers can communicate or interact easily from long distances and different places Moodle is one of the applications of the concepts and mechanisms of teaching and learning that utilize information technology, known as electronic learning concepts or e- learning. Kata Kunci : E-Learning, Covid19, Moodle, LMS, Implementasi, Pasca Covid.